Multiplex PCR use for Staphylococcus aureus identification and oxacillin and mupirocin resistance evaluation - Braoios, Alexandre; Fluminhan, A.; Pizzolitto, Antonio Carlos [UNESP] (My University, 2009)
Oxacillin-resistant Staphylococcus aureus represents a serious problem in hospitals worldwide, increasing infected patients' mortality and morbidity and raising treatment costs and internment time. In this study, the results of using the Multiplex PCR technique to amplify fragments of the genes femA (specific-species), mecA (oxacillin resistance) and ileS-2 (mupirocin resistance) were compared with those of tests conventionally used to identify S. aureus isolates and ascertain their resistance to drugs. Fifty S. aureus strains were isolated from patients receiving treatment at UNOESTE University Hospital in Presidente Prudente, SP, Brazil. The 686 bp fragment corresponding to the gene femA was amplified and detected in all the isolates. On the other hand, the 310 bp fragment corresponding to the mecA gene was amplified in 29 (58%) of the isolates. All of the isolates showed sensitivity to mupirocin in the agar diffusion test, which was corroborated by the lack of any amplicon of the 456 bp fragment corresponding to the ileS-2 gene, in the PCR bands. The conventional tests to identify S. aureus and detect resistance to oxacillin and mupirocin showed 100% agreement with the PCR Multiplex results. The use of techniques for rapid and accurate identification of bacteria and assessment of their resistance may be valuable in the control of infection by resistant strains, allowing the rapid isolation and treatment of an infected patient. However, the results demonstrate that traditional phenotypic tests are also reliable, though they take more time.

Utilização de PCR-multiplex para identificação de Staphylococcus aureus e avaliação da resistência à oxacilina e mupirocina Staphylococcus aureus resistente à oxacilina representa um problema grave em hospitais de todo o mundo, aumentando a morbidade e mortalidade de pacientes infectados e, elevando os custos do tratamento e tempo de internação. Neste trabalho, foram comparados os resultados da técnica de PCR Multiplex para amplificação dos fragmentos dos genes femA (espécie-específico), mecA (resistência à oxacilina) e ileS-2 (resistência à mupirocina) com os resultados da identificação e testes convencionais para avaliação da resistência. Cinqüenta S. aureus foram isolados de pacientes atendidos no Hospital Universitário Dr. Domingos Leonardo Cerávolo da Unoeste, em Presidente Prudente, SP, Brasil. Houve amplificação do fragmento 686 pb, correspondente ao gene femA para todos os isolados. Por outro lado, houve amplificação do fragmento 310 pb correspondente ao gene mecA em 29 (58%) dos isolados. Todos os isolados mostraram sensibilidade à mupirocina observados no teste da difusão em ágar, e também pela ausência de amplificação do fragmento 456 pb, correspondente ao gene ileS-2. Os resultados dos testes convencionais para identificação de S. aureus e avaliação de resistência à oxacilina e mupirocina mostrou 100% de concordância com os resultados da PCR Multiplex. A utilização de técnicas mais rápidas e precisas para identificação e avaliação de resistência pode ser valiosa para o controle de infecção por cepas resistentes, permitindo rápido isolamento e tratamento do paciente. Entretanto os resultados demonstram que testes fenotípicos tradicionais também são confiáveis, apesar do maior tempo de execução. Palavras-chave: PCR Multiplex. Resistência à oxacilina. Staphylococcus aureus. Mupirocina.
Keywords: Mupirocin; Oxacillin-resistant; PCR multiplex; Staphylococcus aureus; bacterial protein; femA protein; ileS 2 protein; oxacillin; penicillin binding protein 2a; pseudomonic acid; unclassified drug; accuracy; agar diffusion; amplicon; antibiotic resistance; bacterial gene; bacterial strain; bacterium identification; bacterium isolate; bacterium isolation; Brazil; controlled study; gene amplification; multiplex polymerase chain reaction; nonhuman; reliability